2019
DOI: 10.18621/eurj.376343
|View full text |Cite
|
Sign up to set email alerts
|

The association of carotid intima-media thickness with body mass index and cortisol level in fibromyalgia syndrome

Abstract: Objective: Patients with fibromyalgia syndrome (FMS) may have the risk for atherosclerotic disease because of chronic stress, disrupted neuroendocrine axis, high BMI and inflammation. This is study aimed to research the stress and the stress-related diseases in patients with FMS by measuring obesity, morning serum cortisol level, and carotid intima-media thickness (CIMT), which is the early indicator of the atherosclerosis. Methods: This is a case-control study. It is included 57 patients who were diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…All these markers had effect size estimators around zero, and the distribution of estimators across studies showed a highly conflicting picture for almost all main outcome measures. For example, approximately half of the studies reported decreased levels of blood cortisol 19,21,22,38,69,89 or ACTH 1,13,81,89 for individuals with FMS compared with FMS-free controls, whereas the other half reported increased levels for the respective outcome measures. 3,6,7,12,14,60 This suggests that these markers do not appear to be altered per se in FMS.…”
Section: Discussionmentioning
confidence: 99%
“…All these markers had effect size estimators around zero, and the distribution of estimators across studies showed a highly conflicting picture for almost all main outcome measures. For example, approximately half of the studies reported decreased levels of blood cortisol 19,21,22,38,69,89 or ACTH 1,13,81,89 for individuals with FMS compared with FMS-free controls, whereas the other half reported increased levels for the respective outcome measures. 3,6,7,12,14,60 This suggests that these markers do not appear to be altered per se in FMS.…”
Section: Discussionmentioning
confidence: 99%
“…No statistically significant difference was found between the two groups. However, the effect of acute phase reactants was not evaluated in this study, and in our research, the result of acute phase reactants on CIMT was also assessed 40 …”
Section: Discussionmentioning
confidence: 92%
“…This suggests that hsCRP may only have a moderating function and may be less causally involved in the pathogenesis of FMS than an expression of possible co-morbidities associated with both FMS and inflammatory processes. A central co-factor that is repeatedly discussed here is obesity, which is associated with both FMS and subclinical inflammatory processes (10,35).…”
Section: Association Between Hscrp Concentrations and Clinical Measuresmentioning
confidence: 98%